Correlation of clinical manifestation of lumbar disc prolapse with magnetic resonance imaging findings among adult patients - Hamna Nasir; Muhammad Usman Sarwar; Sumair Nasim Qureshi; Manqoosh-ur-Rehman; Maqsood, Amjad; Saba Saif (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: The most common cause of low back pain is disc prolapse. Disc prolapse occurs in both gender, but females are more prone to disc degenerative changes. The aim of this study was to determine the correlation between clinical findings and magnetic resonance imaging (MRI) findings of lumbar disc prolapse patients. METHODOLOGY: This study recruited 32 participants of either gender, between the ages of 19 to 65, from the Radiology department of Shalamar Hospital. This study was carried out in six months with follow-up. Only diagnosed patients with lumbar disc prolapse on MRI were recruited. Numeric pain rating scale (NPRS) was used to identify the intensity of pain. History and neurological examinations were done in all diagnosed patients. All the findings of MRI were correlated with the clinical findings at different levels of lumbar vertebrae using Pearson correlation. RESULTS: There was a statistically significant positive correlation of MRI findings with clinical findings in the presence of nerve root compression at the L1-L2 level of lumbar vertebrae. All abnormal findings on MRI did not correlate with clinical findings. There was a significant positive (p-value >0.05) correlation between clinical features (sensations, power and reflexes) and MRI findings at L1, L2, right L3 myotomes and L2 dermatome only. CONCLUSION: There was a no correlation between MRI findings and clinical findings of patients with lumbar disc prolapse except L2 and L3.